FEATURES OF INTRODUCING TECHNOLOGY AND LEARNING IN COOPERATION IN THE SYSTEM OF INCLUSIVE EDUCATION - Nargis Fagimovna Shagieva (Galaxy International Interdisciplinary Research Journal, 2023)
In article is presented the importance of collaborative learning technology in learning process of children needing particular conditions for education as well as cooperative learning methods were identified, which will be considered as most applicable conditions of inclusive education.